Supply Chain Management Model in Digital Geographic for Educational Management in Higher Education Institution - Artaphon Chansamut (ExcelingTech, 2022)
This research aims to develop and to assess supply chain management model in digital geographic for educational management in higher education institution. A sample groups were five experts in supply chain, five experts in geographic information system . All totalling ten experts. The research tool was questionnaire about supply chain management model in digital geographic for educational management in higher education institution . The findings reveal that supply chain management model in digital geographic for educational management in higher education institution is consisted of seven key elements which are main elements suppliers university ,Finished student, customers, Satisfaction And Return. The data analyzed by using arithmetic mean and standard deviation. The model assessment system using Back-Box technique. An evaluation result from experts agreement of supply chain management model in digital geographic for educational management in higher education institution was a high level. It showed that model may be appropriately applied in actual work settings.Â